Least limiting water as a soil indicator in an integrated crop-livestock systems of the Cerrado, Brazil - Tavanti, Renan Francisco Rimoldi [UNESP]; Freddi, Onã da Silva; Marchioro, Vinicius [UNESP]; Tavanti, Tauan Rimoldi [UNESP]; Galindo, Fernando [UNESP]; Wruck, Flávio Jesus; Shiratsuchi, Luciano; Breda, Carlos Cesar (Elsevier, 2019)
The least limiting water range (LLWR) is widely used as an agronomic indicator of soil physical quality, however few studies have reported its spatial variability, mainly in integrated crop-livestock systems (ICL). This study aimed to evaluate the spatial dependence of LLWR and its limits that establish the minimum physical and water restrictions for plant growth in an Oxisol under ICL systems. In addition, to verify correlations between LLWR limits and soil attributes that are commonly used to evaluate the soil compaction state. A georeferenced sampling mesh of 12 ha and 170 randomly distributed points was installed at an experimental station, which specifically studies five ICL systems and a no-tillage system with soybean and maize successions. The soil was sampled in 0.00–0.10 and 0.10–0.20 m layers for determinations of porosity, penetration resistance (PR), bulk density and LLWR. The results showed that LLWR presented spatial dependence and adjusted to the exponential model of semivariance, was positively correlated to macroporosity and total porosity and negatively correlated to bulk density, PR and microporosity. Among the parameters that compose it, the PR curve presented spatial dependence and explained the main changes in soil caused by management systems.
Keywords: Bulk density; Oxisol; Soil and water management and conservation; Soil compaction; Soil penetration resistance